TRADISI PERNIKAHAN ISLAM JAWA PESISIR - Moch. Lukluil Maknun (IBDA` : Jurnal Kajian Islam dan Budaya, 2013)
This research is included in naturalistic research which is intendedto explore the wedding ritual in Pekalongan, a town in the north part ofCentral Java which has a special characteristic. The ritual consists of severalsteps such as nakokke, sangsangan, nentokke dino, pasrahan tukon,malem midodaren, walimah, aqad nikah, resepsi, and balik kloso.Thespeciallity of Pekalongan wedding ritual arev (1) dating after engagement;(2) the brief series of ceremony; (3) the word walimah translated asreading maulid al-barzanji before akad nikah; (4) the couple do not sittogether in the ceremony; (5) a special term bedhol gelung; (6) an activityof balik kloso sisan tilik; (7) a special term nunggak seme; (8) thereare some models of invitation.